2005
DOI: 10.1038/sj.bjc.6602888
|View full text |Cite
|
Sign up to set email alerts
|

Time and chemotherapy treatment trends in the treatment of elderly patients (age ⩾70 years) with small cell lung cancer

Abstract: Platinum-based treatment for small cell lung cancer (SCLC) has been established since 1995. This study investigates treatment outcome of elderly patients (age X70 years) with SCLC over the past 20 years in a large UK cancer centre. Comparison of all-cause survival was assessed in patients presenting between two predefined time periods : 1982 -1994 and 1995 -2003. All the survival analysis were adjusted for stage and performance status and age if appropriate. Survival between different chemotherapy treatment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…There are very little data to guide the management of octogenarians with LS-SCLC. Most of the evidence comes from small retrospective series evaluating outcomes in patients with both limited- and extensive-stage disease, often treated with chemotherapy alone and with limited toxicity outcomes 33, 34, 35. Because of the small number of octogenarians in the CONVERT trial, we cannot draw any firm conclusions on the appropriate management of these patients; however, given the high rates of observed toxicity in this analysis, this should be further investigated in larger studies.…”
Section: Discussionmentioning
confidence: 95%
“…There are very little data to guide the management of octogenarians with LS-SCLC. Most of the evidence comes from small retrospective series evaluating outcomes in patients with both limited- and extensive-stage disease, often treated with chemotherapy alone and with limited toxicity outcomes 33, 34, 35. Because of the small number of octogenarians in the CONVERT trial, we cannot draw any firm conclusions on the appropriate management of these patients; however, given the high rates of observed toxicity in this analysis, this should be further investigated in larger studies.…”
Section: Discussionmentioning
confidence: 95%
“…This supports our evidence that it is not the associated comorbidity rise with age that is wholly responsible for the observed decline in chemotherapy use as patients get older. The apparent reluctance to provide chemotherapy in elderly patients with small-cell lung cancer is not supported by evidence of a poor safety record (Smit et al , 1989; Ludbrook et al , 2003; Yau et al , 2006). …”
Section: Discussionmentioning
confidence: 99%
“…There was no improvement in survival in their NSCLC patients. On the other hand, there was a significant improvement in survival for elderly SCLC patients treated by chemotherapy in the past 20 years [14,15]. Their study included only 26 (8.0%) of 322 patients aged 80 years and over and the MST in the former study period was too short to compare.…”
Section: Discussionmentioning
confidence: 94%
“…Our results in both genders were consistent with this large scale study. O'Brien et al recently reported the trends in the chemotherapeutic outcome in patients age ≥70 years with SCLC and NSCLC [14,15]. There was no improvement in survival in their NSCLC patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation